Forms and functions of translation in foreign language lessons. - Bielykh, Oksana; Charikova, Iryna (Дрогобицький державний педагогічний університет імені Івана Франка, 2024)
Translation acts as a bridge for learners to transition from basic language skills to more advanced proficiency levels, aiding in the gradual acquisition of language competence. The use of translation in foreign language lessons can serve various forms and functions, playing a multifaceted role in language learning. Here are some key forms of translation in foreign language lessons: literal (focuses on word-for-word rendering from one language to another), free (emphasizes conveying the overall meaning and sense of a text rather than sticking strictly to a word-for-word translation), audiovisual (audiovisual materials like videos, movies, or songs in one language might be translated or subtitled into the target language to aid comprehension and language acquisition), and written (involves expressing the meaning of a text or passage from one language into another). These forms of translation perform the following functions: vocabulary expansion (expanding learners' vocabulary by introducing them to new words and expressions in both source and target language); grammar understanding (helping learners understand and apply grammatical structures in the target language by comparing them to the structures in their native language); cultural awareness (learners gain insights into cultural differences and similarities); communication skills (contribute to the development of communication skills, both written and oral, by requiring learners to express ideas accurately in the target language); critical thinking (encourage critical thinking to convey meaning accurately); language comparison (compare linguistic structures and expressions between their native language and the target language, promoting a deeper understanding of both). To ensure a comprehensive and effective language-learning experience, it's essential in our opinion to balance translation in foreign language lessons with other language-learning strategies, which should align with the overall goals and methodologies of foreign language education.
Keywords: translation; foreign language lesson; forms of translation; functions of translation; language skills; 373.3/.5.016:81’25